PENGELOLAAN TAMAN MEDIAN JALAN OLEH DINAS KEBERSIHAN DAN PERTAMANAN KOTA PEKANBARU - Riatno, Roni; Mashur, Dadang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research is to describe The Organizing of Taman Median Jalan in Pekanbaru. Taman Median Jalan is one of Green Places that is needed by the society to maintance the water supply area. The function is also to control the traffic, to restreet, to separate and to control the rapidity. Based on the observation in the field, the problems occur because the officer does not taking care the Taman Median Jalan properly. The aims of the study is to find out and to analyze the organizing of Taman Median Jalan by the officer of Sanitary and Landscape Ministry, then it is also to find out the cause of factors that influences the organizing of Taman Median Jalan in Pekanbaru.The Grand theory used of Amirullah & Budiyono (2004:9) is Management, starts from Planning, Organizing, Actuating and Controlling. The method is Qualitative by using descriptive data analysis. In collecting the data, The researcher used interview, observation and documentation.The results of this study showed that Taman Median Jalan was not organized well by the officer. There were still weaknessess in Planning, Organizing, Actuating and Controlling. There are some main factors that is caused this problem, first, the lock of/or limitation in budgeting, second, because of the human resources, many employeers worked in different place based on their educational background. Third, there were many on qualified employeses (Based on the standard operational procedur) that was established by the government so that Taman Median Jalan was not organized properly.Keywords: Management, Taman Median Jalan